Extension Officers’ Perceptions of Farmers’ Groups in Trinidad, West Indies and Implications for Extension - Marcus N. A. Ramdwar; Valerie Stoute; Wayne G Ganpat (Journal of International Agricultural and Extension Education, 2015)
The Government of Trinidad has highlighted its intentions to renew efforts to promote food production through farmers’ groups, in order to meet the country’s food security goals. Previous planned efforts, from the perspectives of farmers, have been largely unsuccessful (Ramdwar, Stoute & Ganpat, 2014). Therefore, this study sought to investigate the dynamics of farmers’ groups in Trinidad, as perceived by the agricultural extension officers who interact with these groups. Ninety-three percent (n = 123) of the extension officers in Trinidad, who interacted with farmers’ groups, were surveyed. The survey instrument included a 22-item perception scale, which collected information on respondents’ perceptions of: (a) politics and conflict within farmers’ groups; (b) member interactions on their trust issues with other members and with their leaders; and (c) the importance of these groups to agricultural productivity. Exploratory factor analysis (EFA) was used to identify latent factors on the perception scale. These factors were then used as predictors in a regression model of extension officers’ articulated satisfaction with farmers’ groups. This satisfaction is a reflection of the challenges these officers are presumed to face in their delivery of extension services. This study concluded that extension officers’ perceived level of technical capacity was the most impactful predictor in the regression model of satisfaction with farmers’ groups, followed by issues related to the proper functioning of groups. As such, recommendations include improved training for staff and group leaders, as well as improved monitoring
Keywords: extension; perceptions; farmers’ groups; satisfaction; Trinidad